Effect of Elastic Strain Energy on Dynamic Recrystallization During Friction Stir Welding of Dissimilar Al/Mg Alloys - Faliang He; Lei Shi; Chuansong Wu (Metals, 2025)
Dynamic recrystallization (DRX) is a critical microstructural evolution mechanism in friction stir welding (FSW) of metallic materials, directly determining the mechanical properties and corrosion resistance of weld joints. In the field of DRX simulation, conventional models primarily consider intragranular dislocation strain energy as the driving force for recrystallization, while neglecting the elastic strain energy generated by coordinated deformation in polycrystalline materials. This study presents an improved DRX modeling framework that incorporates the multiphase-field method to systematically investigate the role of elastic strain energy in microstructural evolution during FSW of Al/Mg dissimilar materials. The results demonstrate that elastic strain energy can modulate nucleation and the growth of recrystallized grains during microstructural evolution, resulting in post-weld average grain size increases of 0.8% on the Al side and 2.1% on the Mg side in the FSW nugget zone. This research provides new insights into multi-energy coupling mechanisms in DRX simulation and offers theoretical guidance for process optimization in dissimilar material welding.